P22 Obeticholic acid improves transaminases in patients with non-alcoholic steatohepatitis: results from the 18-month interim analysis of the REGENERATE study. (28th September 2020) - Allison, Michael; Sheridan, David; Digpal, Kuldip
Abstract : In the REGENERATE interim analysis, obeticholic acid (OCA) improved liver histology in patients with non-alcoholic steatohepatitis (NASH). Elevated alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels may be associated with fibrosis progression in NASH. We evaluated OCA-mediated improvement in these transaminases, and their utility in monitoring treatment of NASH patients with fibrosis. REGENERATE NASH patients with stage 2 or 3 fibrosis (N=931) were randomized 1:1:1 to placebo, OCA 10 mg, or OCA 25 mg. Changes in ALT and AST (upper limit of normal [ULN], 55 U/L and 34 U/L, respectively) were analysed. Baseline characteristics were well balanced across groups (mean ± SD): age (55±11 years), ALT (79±53 U/L), AST (58±36 U/L); ALT >ULN, 60% (>3×ULN, 8%); AST >ULN, 73% (>3×ULN, 9%). OCA treatment improved transaminase levels at Month 1 through Month 18. In patients with baseline ALT and AST >ULN, ALT normalized in 36% (placebo), 49% (OCA 10 mg), and 66% (OCA 25 mg), and AST normalized in 28%, 42%, and 49% in the respective groups by Month 18. In patients with normal baseline transaminases, elevations to >ULN were greater for placebo than OCA 10 mg or OCA 25 mg. OCA-mediated improvements in transaminases were greater in patients who achieved the REGENERATE primary endpoints (figure 1 ). OCA treatment rapidly improved and sustained ALT and AST, suggesting transaminase may be useful in monitoring treatment response. OCA-treated patients who did not achieve REGENERATE primary endpoints also had marked improvement in transaminases, suggesting longer-term treatment may result in additional histologic improvement.